A critical review of integration analysis of microbial electrosynthesis (MES) systems with waste biorefineries for the production of biofuel and chemical from reuse of CO2. (April 2016) - Sadhukhan, Jhuma; Lloyd, Jon R.; Scott, Keith; Premier, Giuliano C.; Yu, Eileen H.; Curtis, Tom; Head, Ian M.
Abstract: Despite some success with microbial fuel cells and microbial electrolysis cells in recovering resources from wastes, challenges with their scale and yield need to be resolved. Waste streams from biorefineries e.g. bioethanol and biodiesel plants and wastewaters are plausible substrates for microbial electrosynthesis (MES). MES integration can help biorefineries achieving the full polygeneration potentials, i.e. recovery of metals turning apparently pollutants from biorefineries into resources, production of biofuels and chemicals from reuse of CO2 and clean water. Symbiotic integration between the two systems can attain an economic and environmental upside of the overall system. We envision that electrochemical technologies and waste biorefineries can be integrated for increased efficiency and competitiveness with stillage released from the latter process used in the former as feedstock and energy resource recovered from the former used in the latter. Such symbiotic integration can avoid loss of material and energy from waste streams, thereby increasing the overall efficiency, economics and environmental performance that would serve towards delivering the common goals from both the systems. We present an insightful overview of the sources of organic wastes from biorefineries for integration with MES, anodic and cathodic substrates and biocatalysts. In addition, a generic and effective reaction and thermodynamic modelling framework for the MES has been given for the first time. The model is able to predict multi-component physico-chemical behaviour, technical feasibility and best configuration and conditions of the MES for resource recovery from waste streams.